Pengaruh Kualitas Produk, Pelayanan dan Harga terhadap Niat Beli Ulang Konsumen - Wirawan Yudi Asnawa, Anak Agung Gde (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The formulation of the problem and the objectives of this study were to determine the effect of product quality, service quality and price on repurchase intentions at UPTODATE CAFÉ & EATERY in Ubud. The population in this study are all consumers who have shopped at UPTODATE Café & Eatery and the number is unknown. The sample used in this study was 90 respondents who were determined by purposive sampling method. The data in this study were collected through observation, interviews, questionnaires and then tested using multiple linear regression analysis techniques. Based on the results of the study, it can be seen that product quality has a positive and significant effect on repurchase intentions. Service quality has a positive and significant effect on repurchase intentions. Price has a positive and significant effect on repurchase intention. Product quality, service quality, and price have a positive and significant effect on repurchase intentions. The magnitude of the influence of the independent variables on repurchase intention is 63.9%. Looking at the research results, UPTODATE Café & Eatery in the future must be able to improve the quality of its products by paying attention to the taste of the food and drinks being sold. Make sure all products taste right for consumption, not too salty, sweet, or spicy so that consumers can enjoy them and have the desire to buy food and drinks at UPTODATE Café & Eatery again